Distribution and isolation of microalgae for lipid production in selected freshwater reservoirs of northern Thailand - TIPPAWAN PRASERTSIN; YUWADEE PEERAPORNPISAL (Biodiversitas Journal of Biological Diversity, 2018)
Prasertsin T, Peerapornpisal Y. 2018. Distribution and isolation of microalgae for lipid production in selected freshwater reservoirs of northern Thailand. Biodiversitas 19: 343-350. Nong Bau Reservoir and Chiang Saen Lake are considered important freshwater reservoirs of Chiang Rai Province located in northern Thailand. The surrounding areas of these water bodies are host to a range of human activities that influence water quality. Moreover, to date, there are have not been any studies on the water quality and the distribution of microalgae in these places. The physical and chemical parameters of the water quality and microalgae were carried out in Nong Bua Reservoir and Chiang Saen Lake during the months of May, July, and October of 2015. Microalgae were isolated in order to investigate the lipid-producing abilities. Samples collected from Nong Bua Reservoir have revealed the presence of seven divisions, 90 species of algae. Six divisions, 55 species of algae were found in Chiang Saen Lake. The trophic status of the water was evaluated from the main parameters (AARL-PC Score), and it was determined that Nong Bua Reservoir was of meso-eutrophic status and Chiang Saen Lake was of mesotrophic status. Microalgae were isolated from Nong Bua Reservoir and Chiang Saen Lake for the purposes of studying lipid content; 25 and 6 isolations were identified, respectively. The lipid content was highest in Botryococcus braunii (39.25 ± 0.32% dry weight) followed by Ankistrodesmus sp. (26.80 ± 0.44% dry weight) and Coelastrum microsporum (24.95 ± 0.55% dry weight). The lowest lipid content was found in Planktolyngbya sp. (7.25 ± 0.43% dry weight). The indigenous strains of microalgae of Nong Bau Reservoir and Chiang Saen Lake’s can be considered quite promising as model strains in terms of the production of biofuel within the country.